Interakcja w ujęciach teoretycznych – wieloaspektowy charakter zjawiska - Aleksandrzak, Magdalena (Neofilolog, 2017)
The paper concentrates on the notion of interaction with regard to selected theoretical orientations and perspectives. First, the definitions of the three frequently overlapping terms – communication, discourse and interaction – are discussed with particular attention given to their mutual relationships within presented interpretations. Next, the status of interaction in some psychological, sociological and pedagogical orientations is briefly illustrated and a closer look is taken at interaction within cognitive, sociocultural and interactionist approaches to foreign language teaching and learning. The following part of the article focuses on types of interaction in the foreign language classroom. Finally, the selected interpretations of the construct of interactional competence are presented and analysed.